2021
DOI: 10.3390/ijms22105079
|View full text |Cite
|
Sign up to set email alerts
|

Implication of a Key Region of Six Bacillus cereus Genes Involved in Siroheme Synthesis, Nitrite Reductase Production and Iron Cluster Repair in the Bacterial Response to Nitric Oxide Stress

Abstract: Bacterial response to nitric oxide (NO) is of major importance for bacterial survival. NO stress is a main actor of the eukaryotic immune response and several pathogenic bacteria have developed means for detoxification and repair of the damages caused by NO. However, bacterial mechanisms of NO resistance by Gram-positive bacteria are poorly described. In the opportunistic foodborne pathogen Bacillus cereus, genome sequence analyses did not identify homologs to known NO reductases and transcriptional regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Genes belonging to biosynthetic pathways of siroheme and cobalamin had higher average relative abundance in infants diagnosed with neonatal necrotizing enterocolitis (Claud et al 2013), an inflammatory bowel condition affecting premature newborns. The siroheme biosynthesis pathway is upregulated in some human pathogens in response to high nitric oxide (NO) levels likely in relation to the NO detoxification function of nitrite reductase (Porrini et al 2021). Increased NO levels are commonly associated with active inflammation in IBD (Soufli et al 2016).…”
Section: D)mentioning
confidence: 99%
“…Genes belonging to biosynthetic pathways of siroheme and cobalamin had higher average relative abundance in infants diagnosed with neonatal necrotizing enterocolitis (Claud et al 2013), an inflammatory bowel condition affecting premature newborns. The siroheme biosynthesis pathway is upregulated in some human pathogens in response to high nitric oxide (NO) levels likely in relation to the NO detoxification function of nitrite reductase (Porrini et al 2021). Increased NO levels are commonly associated with active inflammation in IBD (Soufli et al 2016).…”
Section: D)mentioning
confidence: 99%
“…NO is cytotoxic and mutagenic for various pathogens and host cells (Yoshitake et al, 2004; Zaki et al, 2005; Zhuang et al, 1998) and plays an important role during infections by limiting microbial proliferation (Porrini et al, 2020). Bacteria express sensor proteins that are able to detect NO and, accordingly, to switch on the expression of enzymes that detoxify NO before it reaches lethal levels (Porrini et al, 2021; Laver et al, 2010). In addition, we previously demonstrated a link between NO-induced bacterial DNA damage and DNA repair by Mfd (Darrigo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that B . cereus is particularly resistant to NO [ 15 , 18 , 45 , 49 ]. Here, we show that the Δ adhB mutant was more sensitive than the wildtype strain to both oxidative and nitric stresses.…”
Section: Discussionmentioning
confidence: 99%